GOURDS OF HUALLAMARCA, ICONOGRAPHY AND FUNCTION: COASTAL GENTLEMEN RECIPROCITY AND SYMBOLS OF POWER - Dolorier, Camilo (2014)
In this paper we analyze contextual and stylistically a set of finely decorated gourds, from the collection of gourds Huallamarca recovered in excavations directed by Dr. Jiménez Borja at huaca Pan de Azúcar in 1958. The gourds have studied simple and naturalistic images that refer to a secular field, agricultural and coastal. The large number of decorated gourds in a context of elite tombs, makes us think of a function, which would go beyond the strictly utilitarian. Piles of pumpkins decorated as large plates, carefully stored inside packages would imply at least that the holder would have a household could face a public activity. Reciprocity as a social, political and economic, would be supported in funerary context quality and new symbols of power that characterize the large coastal chiefs and gentlemen of the initial part of the Late Intermediate Period of the Central Coast.